PEMBERDAYAAN MASJID SEBAGAI PUSAT PENDIDIKAN ISLAM - Ely Suryawati (STAI Sangatta Kutai Timur, 2021)
Mosques and Islamic education are two components that cannot be separated. The two always go hand in hand in the long journey of the dynamics of Islamic education. The purpose of this study is to describe the concept of empowering mosques as centres of Islamic education and optimizing the empowerment of mosques as centres of Islamic education. By answering the various questions above through in-depth analysis and interpretation, it is hoped that this article can be a reference for the development of mosque empowerment and Islamic education in general. The method used is a qualitative research method with a literature study. The analysis used is the Miles & Huberman interaction model. As a result, the concept of empowering mosques as centres of Islamic education is a reflection of the function of mosques other than as a means of praying together five times a day. This is where the need to mobilize ta'lim assemblies, empower youth, organize various pieces of training and seminars, make mosques a centre of knowledge, increase cooperation, empower the poor, and foster mosque independence. Optimizing the empowerment of mosques as centres of Islamic education must continue to be pursued by improving mosque management, optimizing the religious field, youth sector, social community field, cultural field, and economic field. Thus, the empowerment of mosques as centres of Islamic education, with various concepts that have been explained, good mosque management, and optimization of various fields in mosques is not only discourse but is already at the level of real action for the welfare of the mosque. and implementation of the empowerment of mosques as centres of Islamic education.